Nucleotide excision repair is not induced in human embryonic lung fibroblasts treated with environmental pollutants - Rossner, Pavel; Mrhalkova, Andrea; Uhlirova, Katerina; Spatova, Milada; Rossnerova, Andrea; Libalova, Helena; Schmuczerova, Jana; Milcova, Alena; Topinka, Jan; Sram, Radim J (PloS one, 2013)
The cellular response to genotoxic treatment depends on the cell line used. Although tumor cell lines are widely used for genotoxicity tests, the interpretation of the results may be potentially hampered by changes in cellular processes caused by malignant transformation. In our study we used normal human embryonic lung fibroblasts (HEL12469 cells) and tested their response to treatment with benzo[a]pyrene (B[a]P) and extractable organic matter (EOM) from ambient air particles <2.5 µm (PM2.5) collected in two Czech cities differing in levels and sources of air pollution. We analyzed multiple endpoints associated with exposure to polycyclic aromatic hydrocarbons (PAHs) including the levels of bulky DNA adducts and the nucleotide excision repair (NER) response [expression of XPE, XPC and XPA genes on the level of mRNA and proteins, unscheduled DNA synthesis (UDS)]. EOMs were collected in the winter and summer of 2011 in two Czech cities with different levels and sources of air pollution. The effects of the studied compounds were analyzed in the presence (+S9) and absence (-S9) of the rat liver microsomal S9 fraction. The levels of bulky DNA adducts were highest after treatment with B[a]P, followed by winter EOMs; their induction by summer EOMs was weak. The induction of both mRNA and protein expression was observed, with the most pronounced effects after treatment with B[a]P (-S9); the response induced by EOMs from both cities and seasons was substantially weaker. The expression of DNA repair genes was not accompanied by the induction of UDS activity. In summary, our results indicate that the tested compounds induced low levels of DNA damage and affected the expression of NER genes; however, nucleotide excision repair was not induced.
Keywords: Gene Expression Regulation; RNA, Messenger; adukty DNA; Cell Line; fibroblasty; Particulate Matter; pevné částice; DNA-Binding Proteins; Cell Proliferation; Fibroblasts; plíce; látky znečišťující životní prostředí; xeroderma pigmentosum - protein skupiny A; DNA vazebné proteiny; Xeroderma Pigmentosum Group A Protein; polycyklické aromatické uhlovodíky; látky znečišťující vzduch; DNA Repair; Lung; oprava DNA; lidé; Humans; DNA Adducts; regulace genové exprese; buněčné linie; proliferace buněk; Environmental Pollutants; messenger RNA; Polycyclic Aromatic Hydrocarbons; Air Pollutants